2018
DOI: 10.1002/jmor.20847
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural investigations on spermatogenesis and spermatozoan morphology in the endangered Adriatic sturgeon, Acipenser naccarii (Chondrostei, Acipenseriformes)

Abstract: Spermatogenesis was investigated in the Adriatic sturgeon, Acipenser naccarii, by light and electron microscopy. The testis of the unrestricted type had a germinal compartment composed of lobules containing germ cells and Sertoli cells, and separated by a basal lamina from the interstitial compartment, in which Leydig and myoid cells were detected for the first time in Acipenseridae. Spermatogenesis occurred in spermatocysts produced when Sertoli cells became associated with type A spermatogonia of subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…And it corresponded to the stage of Spermatid II in the present study. A recent study on Adriatic sturgeon (Acipenser naccarii) also showed that the flagellum occurred in early spermatids, although spermiogenesis was not clearly divided (Grandi et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…And it corresponded to the stage of Spermatid II in the present study. A recent study on Adriatic sturgeon (Acipenser naccarii) also showed that the flagellum occurred in early spermatids, although spermiogenesis was not clearly divided (Grandi et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Siberian sturgeon males in this study is potentially capable of the final maturation of male gametes at the age of 4 years. Although not all those males were tested, several 4-year-old males subjected to induced hormonal spermiation trials were proven to be able to provide a good quality of sperm that can be highly compatible with artificial insemination trials (data not shown), suggesting that, at least in a certain portion of males, the process of not only spermatogenesis but also functional spermiogenesis could be completed by this age (Schulz et al, 2010;Dzyuba et al, 2017;Grandi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%